The Board of Director Compensation and Corporate Tax Aggressiveness: Evidence from Indonesia - Lidia Sari Christina; Heru Tjaraka (AIBPM Publisher, 2018)
This paper aims to investigate the influence of the board of director compensation on tax aggressiveness. The board of director compensation in this research is measured by the logarithms of total board of director compensation while tax aggressiveness is measured by the effective tax rate. Data analyzed consisted of 59 manufacturing companies from 20142016 that listed on Indonesia Stock Exchange, and this research used 169 observations data. Data was collected then processed by multiple regression analysis techniques. After all, the final result showed that the board of director compensation has positive and significant influence on tax aggressiveness. Keywords: Board of directors, compensation, tax aggressiveness